Corpo – escrita no balé: para repensar o corpo doce da bailarina da caixinha de música em uma pesquisa em educação e arte - Silva, Daniela Grieco Nascimento e (2017)
This research tries to think, through body-writing, about questions related to the gender roles built in the world of ballet, more specifically to the body of the classical ballerina throughout time. Body – writing is a text that the dancer writes with her body movements, weaving subjective corporal scenarios that are captured by the eye of the viewer, thus establishing a potent and sensitive experimental play of creation. Since women predominate in the practice of ballet their body was represented through the relations of power determined by society and culture. A sweet body was created for her, on which hegemonic masculine speeches are written about femininity, creating the myth of the eternal feminine and building the image of the ballerina in association to the women of the romantic period, when the symbolical law of domination strongly carved itself into the female bodies and consciences, creating the image of the music-box ballerina, a symbol of beauty, grace, tenderness, purity and submission. In order to enable a problematization and a greater approach of ballet to contemporaneity, a collective creative process was proposed to the twelve female dancers and the one male dancer of the Royale Dance Company on the theme “women in the Brazilian military dictatorship period in order to investigate questions related to gender roles and to propitiate weighing on women’s empowerment. Having auto-ethnography as support, from March to November of 2016, the dancers realized bibliographical research, expositions, movie discussions, as well as Creative process workshops that originated the spectacle #emmemoriadelas presented in December at the Theatro Treze de Maio, in Santa Maria, RS. The whole process was registered by notes on the field journal, photographs and recording of the spectacle itself, as well as a questionnaire with questions pertinent to the research for the dancers. It was possible to comprehend that the process of collective creation led to different problematizations over the theme under study, more discernment about the female situation, greater social and political commitment. Thus, the dancers realize their social roles as interventional agents in their surroundings and that ballet is capable of weaving contemporary scenarios with their movements, in order to create other narratives from the body - writing. As a result of this research it is possible to mention the artistic and educational actions produced by the NGO Royale School of Dance and Social Integration through the collective creative process of the spectacle #emmemoriadelas, as well as the women’s empowerment in ballet as way of rethinking the sweet body of the music-box ballerina as contribution to the fields of education and arts.